(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Anaemia is a condition that occurs when haemoglobin levels decrease below normal and a lower-than-normal number of healthy red blood cells are produced. A newly identified iron regulator, hepcidin reveals the body’s iron status and demand for erythropoiesis to the intestine which modulates intestinal iron absorption. Hepcidin plays a significant role in the iron regulatory system as it naturally binds to ferroportin which is the cellular iron expoter. The hepcidin was docked with bioactive compounds in catechin, chlorogenic acid, T. aestivum grass and 2,4 dihydroxy benzaldehyde in P. betel leaves. The aim of the current study is to investigate the interaction of bioactive compounds with hepcidin through molecular docking. All three bioactive compounds revealed significant interaction with hepcidin. Catechin showed highest binding energy (-7.1 Kcal/mol) as compared to cholorogenic acid and 2,4 dihydroxy benzaldehyde.